The effects of cryopreservation on the acrosome structure, enzyme activity, motility, and fertility of bovine, ovine, and goat sperm - Sun, Wei (Anim Reprod, 2021)
The study was designed to investigate the effects of cryopreservation on bovine, ovine, and goat sperm motility, acrosome structure, enzyme activity, and fertilization ability. Percentage of sperm with hyaluronidase enzyme (HYD) activity was detected by a modified sodium hyaluronate-gelatin membrane. The N-α-benzoyl-DL-arginine-p-nitroanilide (BNPNA) method was used to assess the sperm acrosome enzyme (ACE). The mean percentage of sperm acrosome integrity dropped significantly (P < 0.01) after cryopreservation. The ACE activity of bovine sperm (100.48) was higher (P < 0.01) than that of ovine (57.88) or goat sperm (50.30), while the percentage of sperm with HYD activity of bovine (71.10%) and ovine (67.60%) sperm was higher than that of goat sperm (58.52%) after cryopreservation (P < 0.01). Sperm motility was positively correlated with the activity of the two acrosome enzymes before and after cryopreservation (P < 0.01). Cryopreservation had a negative effect on acrosomal morphology, motility, and acrosomal enzyme activity in their sperm. The fertilization ability of ovine and goat sperm decreased significantly after cryopreservation, but that of frozen bovine sperm did not differ significantly when compared with fresh sperm. There was no significant difference between ovine and goat sperm indices, except for percentage of sperm with HYD activity.